Cost-effectiveness study of treatment with biologic disease-modifying antirheumatic drugs in adult patients with active ankylosing spondylitis - R. O. Dreval (Современная ревматология, 2021)
Objective: to conduct a cost-effectiveness study of major biologic disease-modifying antirheumatic drugs (bDMARDs) used for the treatment of ankylosing spondylitis (AS) in Russian health care system with the focus on the new effective drug netakimab (NTK).Patients and methods. Based on the available meta-analysis, a Markov model for therapy was constructed using reference drugs. Then, based on the simulation results, a Cost-Effectiveness Analysis (CEA) and a Budget Impact Analysis (BIA) were carried out. The robustness of the result has been confirmed by several sensitivity analyzes.Results and discussion. NTK showed an advantage in CEA, including the cases when the direct costs of therapy were lower for the reference drug (which shows the greater efficacy of NTK). According to the BIA, the extension of NTK administration in naive patients was consistently associated with a decrease in the budgetary burden. Sensitivity analyzes confirmed the robustness of the result.Conclusion. NTK has clinical and economic advantage in the treatment of AS, it is attractive in terms of both patient's and health care benefit in general. More extensive use of NTK can save more than 5 billion RUB.